Taxonomie rodu Stigeoclonium v ČR - Caisová, Lenka (Jihočeská univerzita, 2007)
The genus Stigeoclonium is taxonomically very problematic. The relationships between species of this genus are very little known. There are only a few studies that deal with only morphological revision of the genus Stigeoclonium. Hovewer, up to now no phylogenetic analysis of this genus exists. This study summarizes the knowledge about the genus Stigeoclonim in the Czech Republic and shows the first phylogenetic analysis of this genus.
A taxonomy of the genus Stigeoclonium in the Czech Republic
Keywords: Stigeoclonium; taxonomie; zelené řasy; fylogenetické analýzy; Česká republika; Stigeoclonium; taxonomy; green algae; phylogenetic analysis; Czech Republic